Muse: A Musically Inspired Game To Teach Arrays and Linked Lists (International Conference on Computers in Education, 2017)
Data structures is an important area of knowledge in computer science that is often difficult to understand for high school students. There has been a lot of research in computer science education around the subject of programming. Hence, it becomes imperative to explore the domain of data structures as well. With this work, we have looked into an active pedagogical approach for facilitating learning of data structures in school. This approach has been implemented by means of an interactive game. The game aims to teach arrays and linked lists through activities based on the principle of compare and contrast. The innovation in the game is the use of musical notes to teach operations in arrays and linked lists. The game was evaluated with 27 students across 8th, 9th and 10th grades using a questionnaire. The results of the evaluation showed that the group of students who learnt about arrays and linked lists through the game scored an average of 81.5% of the total marks while the other group scored an average of 72% of the total marks.